Determination of Slope Instability Using Spatially Integrated Mapping Framework - Baharuddin I.N.Z.; Omar R.C.; Roslan R.; Khalid N.H.N.; Hanifah M.I.M. (Institute of Physics Publishing, 2023)
Engineering research; Infiltration; Land use; Machinery; Plasma stability; Regional planning; Stability; Framework; Integrated; Regional analysis; Slope; Slope instability; Soil investigation; Spatially; Tropical forest; Mapping